Peaceful and Tolerant Solutions to Conflict Resolution from the Perspective of the Holy Qur’an: Thematic Study - Abu Mujadidul Islam (Pascasarjana Universitas Wahid hasyim Semarang, 2017)
AbstractThis paper discusses about the social conflict in terms ofsolutions, including the Koran specifically, also discusses aboutthe kinds of social and religious conflict, whether conflictsbetween religions and between religious communities. Theapproach taken in this research is objective interpretativeapproach while the method used in this study is a qualitative.This research concludes that the Qur'an recognizes the conflictalthough it is considered a factor of negative factors in society,and recognizes that the conflict in the laws of God in theuniverse because the dispute is based on the reality of diversityand pluralism in this life. Al-Qur’an also shows us a number ofways to pay for these conflicts, management and turn it into apeaceful relationship and friendship save society from fallinginto the conflict in each of the Meccan and Medina verses.Keywords: tolerance; peaceful; temporary thinking